Cost-effectiveness of digoxin, pacing, and direct current cardioversion for conversion of atrial flutter in neonates. (6th March 2018) - Prasad, Deepa; Steinberg, Joni; Snyder, Christopher
Abstract: Introduction: Newborn atrial flutter can be treated by medications, pacing, or direct current cardioversion. The purpose is to compare the cost-effectiveness of digoxin, pacing, and direct current cardioversion for the treatment of atrial flutter in neonates. Materials and methods: A decision tree model was developed comparing the efficacy and cost of digoxin, pacing, and direct current cardioversion based on a meta-analysis of published studies of success rates of cardioversion of neonatal atrial flutter (age<2 months). Patients who failed initial attempt at cardioversion progressed to the next methodology until successful. Data were analysed to assess the cost-effectiveness of these methods with cost estimates obtained from 2015 Medicare reimbursement rates. Results: The cost analysis for cardioversion of atrial flutter found the most efficient method to be direct current cardioversion at a cost of $10 304, pacing was next at $11 086, and the least cost-effective was digoxin at $14 374. The majority of additional cost, regardless of method, was from additional neonatal ICU day either owing to digoxin loading or failure to covert. Direct current cardioversion remains the most cost-effective strategy by sensitivity analyses performed on pacing conversion rate and the cost of the neonatal ICU/day. Direct current cardioversion remains cost-effective until the assumed conversion rate is below 64.6%. Conclusion: The most cost-efficient method of cardioverting a neonate with atrial flutter is direct current cardioversion. It has the highest success rates based on the meta-analysis, shorter length of stay in the neonatal ICU owing to its success, and results in cost-savings ranging from $800 to $4000 when compared with alternative approaches.